A Review of Cognitive Disorders in Attention Deficit Hyperactivity Disorder with Emphasis on Executive Functions and Brain Structures: Cognitive Disorders in ADHD - Roshannia, Somayeh; Maleki-Karamolah, Somayeh; Akhlaghi , Zhamak; Kordestani-Moghadam, Parastou (International Clinical Neuroscience Journal, 2021)
Attention deficit hyperactivity disorder is one of the most common childhood neurodevelopmental disorders characterized by levels of attention deficit disorder, irregularity, or hyperactivity/impulsivity. Some research has shown that only a fraction of children with attention deficit hyperactivity disorder, and not all of them, suffer from performance-related impairments; but recently it has become clear that all people with this disorder are impaired in executive functions. In other words attention deficit hyperactivity disorder is fundamentally a developmental disorder of executive functions. Poor inhibitory control, continuous attention deficit, problem-solving, and behavioral inhibition are cognitive deficits in children with attention deficit hyperactivity disorder that they are exhibit in tests related to executive functions. Evidences suggest differences in some executive functions, such as behavioral inhibition between boys and girls. Attention deficit hyperactivity disorder has its neurobiological basis and most empirical evidence indicates delayed frontal lobe development in children with this disorder. Therefore, the purpose of this study was to review cognitive disorders in children with attention deficit hyperactivity disorder with an emphasis on executive functions.